Specificity, propagation, and memory of pericentric heterochromatin. Issue 8 (18th August 2014) - Müller‐Ott, Katharina; Erdel, Fabian; Matveeva, Anna; Mallm, Jan‐Philipp; Rademacher, Anne; Hahn, Matthias; Bauer, Caroline; Zhang, Qin; Kaltofen, Sabine; Schotta, Gunnar; Höfer, Thomas; Rippe, Karsten
Abstract The cell establishes heritable patterns of active and silenced chromatin via interacting factors that set, remove, and read epigenetic marks. To understand how the underlying networks operate, we have dissected transcriptional silencing in pericentric heterochromatin (PCH) of mouse fibroblasts. We assembled a quantitative map for the abundance and interactions of 16 factors related to PCH in living cells and found that stably bound complexes of the histone methyltransferase SUV39H1/2 demarcate the PCH state. From the experimental data, we developed a predictive mathematical model that explains how chromatin‐bound SUV39H1/2 complexes act as nucleation sites and propagate a spatially confined PCH domain with elevated histone H3 lysine 9 trimethylation levels via chromatin dynamics. This "nucleation and looping" mechanism is particularly robust toward transient perturbations and stably maintains the PCH state. These features make it an attractive model for establishing functional epigenetic domains throughout the genome based on the localized immobilization of chromatin‐modifying enzymes.